Host card emulation with tokenisation: security risk assessment - Fonte, Luís Pereira da (2019)
Host Card Emulation (HCE) is an architecture that provides virtual representation of contactless cards, enabling transactional communication for mobile devices with Near-Field Communication (NFC) support without the need of Secure Element (SE) hardware. Performing the card emulation mainly by software, usually in wallet-like applications which store payment tokens for enabling transactions, creates several risks that need to be properly evaluated in order to be able to materialise a risk-based implementation. This paper describes the HCEt and proposes the identification and assessment of its risks through a survey conducted to specialists in the subject matter, analysing the model from the point of view of a wallet application on a mobile device that stores payment tokens to be able to perform contactless transactions. Despite the increasing complexity and specialisation of software, hardware, and the respective technical cyberattacks we conclude that the human nature remains the easiest to exploit, with greater gains.